Bahcesehir long-term population-based screening compared toNational Breast Cancer Registry Data: effectiveness of screeningin an emerging country - (:unkn) unknown (My University, 2021)
PURPOSEWe aimed to show the effects of long-term screening on clinical, pathologic, and survival outcomes in patients with screen-detected breast cancer and compare these findings with breastcancer patients registered in the National Breast Cancer Registry Data (NBCRD).METHODSWomen aged 40–69 years, living in Bahcesehir county, Istanbul, Turkey, were screened every2 years using bilateral mammography. The Bahcesehir National Breast Cancer Registry Data(BMSP) data were collected during a 10-year screening period (five rounds of screening). BMSPdata were compared with the NBCRD regarding age, cancer stage, types of surgery, tumor size,lymph node status, molecular subtypes, and survival rates.RESULTSDuring the 10-year screening period, 8758 women were screened with 22621 mammograms.Breast cancer was detected in 130 patients; 51 (39.2%) were aged 40–49 years. The comparisonof breast cancer patients in the two programs revealed that BMSP patients had earlier stages, higher breast-conserving surgery rates, smaller tumor size, more frequent negative axillarynodal status, lower histologic grade, and higher ductal carcinoma in situ rates than NBCRD patients (p = 0.001, for all).CONCLUSIONThese results indicate the feasibility of successful population-based screening in middle-incomecountries.